Floristic diversity and demographic structure of the Sidi R'Ghies forest, north-eastern of Algeria - MALIKA RACHED-KANOUNI; KARIMA KARA; Hichem Khammar; LABED ABABSA (Society for Indonesian Biodiversity, 2020)
Abstract. Rached-Kanouni M, Kara K, Khammar H, Ababsa L. 2020. Floristic diversity and demographic structure of the Sidi R'Ghies forest, north-eastern of Algeria. Biodiversitas 21: 875-881. In Algeria, the degradation of the ecosystems induces a loss of biodiversity and an increase in the adverse effects of climate change and anthropogenic actions, especially at the level of the ecosystems of semi-arid zones. This study aims to determine the floristic composition and demographic structures of different stands within the Sidi R'Ghies forest, north-east of Algeria. Data were collected using floristic surveys, diameter measurements at 1.30 m and total height for trees in four plots with size for each plot of 1000 m2. The diversity indices have been calculated on the basis of specific frequencies. The analysis revealed a low floristic richness with 6 woody species belonging to 5 families with the most dominant are the Cupressaceae and Fagaceae (29%). The low density of woody trees (97.78 individuals/ha) was found in Plot 1 and the high density of 205.56 individuals/ha was found in Plot 4. The diametric structure adjusts to the Weibull distribution and shows a predominance of young individuals. The distribution of trees in height classes shows a single distribution with an asymmetric curve. This positive distribution reveals a predominance of individuals with a height between 2 and 8 m (sapling to mature stage). This work, which provides an overview of the state of the floristic diversity of the Sidi R’Ghies forest, allows taking appropriate measures to safeguard our plant resources.